Vegetative Growth Response of Tomato (Solanum lycopersicum L) Due to Different Doses of Horse Manure Bokashi - Ahmad Raksun; I Wayan Merta; I Gde Mertha (Jurnal Biologi Tropis, 2021)
Tomato is an annual plant that can grow well in the territory of Indonesia. Tomato growth is determined by the availability of nutrients in the growing media. The availability of nutrients can be increased by fertilization. Research on Vegetative Growth Response of Tomato (Solanum lycopersicum L) Due to Different Doses of Horse Manure Bokashi has been carried out in Bajur Villagre, West Lombok Regency. This research aims to determine: (1) the effect of different doses of horse manure bokashi to the growth of tomato, (2) the optimum dose of horse manure bokashi that need to be given to agricultural land so that tomato can grom optimaly. In this research, a completely randomized design was used. Horse manure bokashi treatment consisted of 6 levels with 4 replications.ÃÂ  The growth parameters were stem height, number of leaves, leaf lenght and leaf widh which were measured 42 days after planting. The research data were analyzed by analysis of variance. The result showed that: (1) different doses of horse manure bokashi significantly affected stem height, number of leaf, leaf lenght and leaf width of tomatoes, (2) the optimum dose of horse manure bokashi that need to be given to agricultural land so that tomato can grom optimaly is 1,6 kg for 1 m2 of agricultural land.